1968
DOI: 10.1007/bf01258169
|View full text |Cite
|
Sign up to set email alerts
|

A new bovine adenovirus

Abstract: In the United States Klein, Early and Zellat (1959) and Klein, ZeUat and Michaelson (1960) isolated the bovine adenovirus type 1 and type 2.In England Darbyshire, Dawson, Lamont, Ostler, and Pereira (1965) isolated bovine adenovirus type 3 and in Hungary Bartha and Alddsy (1966) isolated bovine adenovirus type 4 and type 5.In our laboratory an adenovirus has been isolated as a latent virfi~s : from primary calf testes cell cultures. Its cytopathic effect is slow and the virus titre is low e.g. 102.5 TCIDs0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Isolations were from apparently healthy cattle (9) and from a variety of clinical syndromes that include conjunctivitis (24), pneumonia (7), pneumoenteritis (1), and diarrhea (14). Latent adenoviruses have also been isolated from primary bovine testes (4,23) and bovine embryonic kidney cell cultures (20).…”
Section: Introductionmentioning
confidence: 99%
“…Isolations were from apparently healthy cattle (9) and from a variety of clinical syndromes that include conjunctivitis (24), pneumonia (7), pneumoenteritis (1), and diarrhea (14). Latent adenoviruses have also been isolated from primary bovine testes (4,23) and bovine embryonic kidney cell cultures (20).…”
Section: Introductionmentioning
confidence: 99%
“…TANAKA and coworkers (11) and I•ABA et al (5) propagated bovine adenovirus type 4 and another isolate to be differentiated (8) from blood of calves with rhinitis, diarrhea and fever. RONDtIUIS (9) and SoHoPov et al (10) found contaminating bovine adenoviruses in cell cultures from calf kidney and testis. The latter strains were not related to serotypes 1--5, and were independently registered as serotype 6.…”
mentioning
confidence: 97%
“…Many bovine adenoviruses have been isolated from apparently normal animals. The B6 prototype strain came from a calf testes cell culture (Rondhuis, 1968), as did B4 strains (Bartha and Csontos, 1969) and B4 and B6 (Phillip and Sands, 1972) strains. Isolations have also been made under conditions not associated with adenoviruses, such as the isolation of a type 6 virus from the lymph node of a leukotic cow (Mayr et al, 1970).…”
Section: Association With Diseasementioning
confidence: 99%